Wound dehiscence in a sample of 1 776 cystectomies: identification of predictors and implications for outcomes. (18th July 2015) - Meyer, Christian P.; Rios Diaz, Arturo J.; Dalela, Deepansh; Hanske, Julian; Pucheril, Daniel; Schmid, Marianne; Trinh, Vincent Q.; Sammon, Jesse D.; Menon, Mani; Chun, Felix K.H.; Noldus, Joachim; Fisch, Margit; et al.
Abstract : Objective: To investigate the incidence and predictors of wound dehiscence in patients undergoing radical cystectomy (RC). Patients and Methods: In all, 1 776 patient records with Current Procedural Terminology (CPT) codes for radical cystectomy (RC) were extracted from the American College of Surgeons National Quality Improvement Program (ACS‐NSQIP) between 2005 and 2012. Stratification was made based on the occurrence of postoperative wound dehiscence, defined as loss of integrity of fascial closure. Descriptive and logistic regression models were used to identify predictors of postoperative wound dehiscence. The implications of wound dehiscence on peri‐ and postoperative outcomes such as complications, mortality, prolonged length of stay (>11 days), and prolonged operative time (>411 min), were assessed. Results: Of 1 776 patients analysed, 57 (3.2%) had a documented wound dehiscence. In multivariable analyses, chronic obstructive pulmonary disease (odds ratio [OR] 2.0, 95% confidence interval [CI] 1.0–4.0; P = 0.03) and high body mass index (OR 2.3, 95% CI 1.3–4.4; P = 0.008) were significant predictors of wound dehiscence. While female gender had significantly lower proportions of wound dehiscence, multivariable analyses did not confirm this (OR 0.4, 95% CI 0.4–1.4; P = 0.75). Conclusions: Our study is the first to identify predictors of wound dehiscence after RC in a large, contemporary multi‐institutional cohort. Identifying patients at risk of postoperative wound complications may guide the use of preventative measures at the time of surgery.